Wielopoziomowy model bezpieczeństwa systemu informatycznego zarządzania - Matouk, Kamal (Layer Security Model of the Management Information System, 2005)
The article presents issues relating to Management Information Systems protection strategy in enterprises and highlights the important of planning system security and its content. Therefore, I propose a layer protection system which I believe that will help enterprises in planning their security system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 416-423